2015
DOI: 10.1021/acs.joc.5b00133
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Hydroxymethylaminocyclitols as Glycosidase Inhibitors

Abstract: Four series of C 7 N aminocyclitol analogues of glucose were synthesized by stereocontrolled epoxide opening of hydroxyl protected forms of the cyclohexane epoxides cyclophellitol and 1,6epi-cyclophellitol. The resulting hydroxymethyl substituted aminocyclitols were tested as glycosidase inhibitors. Cyclitols having an amino group in an α configuration at a position equivalent to the anomeric in the sugar were found to be low micromolar inhibitors of the α-glucosidase from baker's yeast with K i 's near to 2 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…The introduction of ac arboxamide group at the N1 positioni nduces an increase in the inhibitory activity against a-glucosidase. [29] Another strategy to modify quercitol is replacement of the 1'-hydroxy group with an amino group. [26] Notably,t he racemate of 50 also possesses higher activity than the levo enantiomer.…”
Section: Other Sugar-mimic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of ac arboxamide group at the N1 positioni nduces an increase in the inhibitory activity against a-glucosidase. [29] Another strategy to modify quercitol is replacement of the 1'-hydroxy group with an amino group. [26] Notably,t he racemate of 50 also possesses higher activity than the levo enantiomer.…”
Section: Other Sugar-mimic Compoundsmentioning
confidence: 99%
“…SAR studies indicatet hat the position of the amino and hydroxy groups is crucial for their inhibitory activity,a nd the lipid chain is also ac ritical structure. [29] Another strategy to modify quercitol is replacement of the 1'-hydroxy group with an amino group. Following this guideline, epimers 56 and 57 have been synthesized and evaluated as potent rice AGIs.…”
Section: Other Sugar-mimic Compoundsmentioning
confidence: 99%
“…The amino‐carbasugar structural motif of aminocyclitols is particularly important since it is found in a variety of biologically active compounds like aminoglycoside antibiotics and alkaloids . In addition, aminocyclitol derivatives have been reported as inhibitors of glycosidases . Aminocyclitols 33 were obtained by McMurry coupling from the fully protected aldehyde 34 , obtained in turn by oxidation of diol 35 generated via reductive ring opening of 36 with LiAlH 4 .…”
Section: Endocyclic Oxygen Replacementmentioning
confidence: 99%
“…Firstly, due to the lack of structural information about chitin synthase, the details of the chitin synthesis process remain elusive, but researchers have found that β-(1-4)-glycosidic bond formation between aminosaccharides with inversion of the configuration at the anomeric center occurs in the transfer of GlcNAc residues to chitin [23]. Natural CSIs such as trehazolin [35,36,37,38], salbostatin [39,40,41], and validoxylamine [42,43,44], possess a similar structure to UDP-GlcNAc, so we can hypothesize that chitin synthase perhaps mistakes these natural CSIs for chitin synthetic precursors to complete chitin synthesis resulting in interruption of chitin formation. Secondly, in the GlcNAc part of the chitin precursor, the hemiacetal hydroxyl group and amino group are located on the 1- and 2- positions of the glucose ring, whereas these two groups are arranged at 2- and 1- positions in the sugar ring of the abovementioned natural CSIs.…”
Section: Introductionmentioning
confidence: 99%